On thermodynamic approach to the problem of solidification of a diluted binary melt - Kanischev, V.N. (Functional Materials, 2006)
An approach to the problem of mass transfer in a solidifying binary melt is considered based on the principle of the least energy dissipation. A simple example has been presented demonstrating the good prospects of that approach to the solidification problems. Рассмотрен подход к проблеме массопереноса в затвердевающем бинарном расплаве, основанный на принципе наименьшего рассеяния энергии. На простом примере показана перспективность такого подхода к проблемам затвердевания. Розглянуто пiдхiд до проблеми масопереносу у бiнарному розплавi при його твердiннi, оснований на принципi найменшого розсiяння енергiї. На простому прикладi показано перспективнiсть такого пiдходу до проблем твердiння.